Programa de estrategias didácticas para desarrollar el pensamiento crítico en estudiantes de quinto grado de primaria de la Institución Educativa Rafael Narváez Cadenillas - Trujillo, 2018 - Angeldonis Hurtado, Jannet Catherine (2019)
The purpose of the present investigation was determining in what measure the application of the program of didactic strategies improve the critical thought in the students of fifth degree of the Educational Institution Rafael Narváez Cadenillas, Trujillo 2018. The one for which a sample was used 49 students, being the section B ( 22 ), the experimental group and the section To ( 27 ) students the control group. The kind of sampling was intentional guy's probabilistic no. In like manner, the Test To Evaluate the Critical Thought was used like instrument of measurement ( TEPC ), it is you were composed of 15 items. The application of the Program had a duration brought nearer of two months, besides he was developed taking areas into account Ciencia's curriculares and technology, social Personal and Educación Religious. Data were processed using the descriptive and inferential statistics. In order to find the significant difference between the stockings of both groups, the t for independent samples used the proof itself. The result evidences that the critical or tabular value of t ( 2.01 ) is experimental t youngerly ad valorem ( 21.70 ), what it means than the application of the program of didactic strategies if the critical thought in the students of fifth degree of the Educational Institution improves significantly Rafael Narváez Cadenillas, Trujillo 2018, the alternative hypothesis is accepted and the null hypothesis is refused.